Growing Historical Awareness among the Young Generation of the Indonesian Nation - Yuriska Septiana Wulan Dari; Novinda Triyan Rachmadani; Achmad Khiyarul Wahdi; Adelliya Cahyani; Rita Gusman; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2022)
Basically, history learning is a science that systematically studies the dynamics of society in the past, provides an assessment of the present, the results of which become the basis for the future. History can make the younger generation aware of the richness of life that occurs in the surrounding community, so that the younger generation can understand and interpret historical events. The purpose of this research is to inculcate historical awareness for the younger generation which is important in the life of the nation and the state, apart from being the identity of the origin of a place, it can also know the pattern of people's lives and cultural diversity in various nations and countries. Referring to the discussion, it is necessary to develop historical learning that can invite the younger generation to be critical and can benefit from studying history, so that it can create a sense of pride and will grow or raise awareness of nationalism in the young generation of the Indonesian nation.